Adsorption performance using corn stalk as activated carbon to reduce heavy metals concentration in aqueous solution - Abu Dzar Mohd Isham (2014)
Heavy metals that discharge from industrial factory have leading to water pollution in the environment. Various methods had been applied in order to reduce the amount of heavy metals such as membrane filtration, ion exchange treatment, chemical precipitation and adsorption. Among the various methods, adsorption method is the most effective method to reduce the amount of heavy metals. This research was carried out to know the potential of corn stalk as activated carbon to reduce heavy metals concentration in aqueous solution. The characteristic of cornstalk as activated carbon was evaluated by using proximate analysis and scanning electron microscopy. Two different parameters which are adsorbent weight and contact time were studied to reduce the percentage of heavy metals in aqueous solution. From the experiment conducted, the corn stalk can be used as adsorbent because it can reduce the percentage of heavy metals solution up to 96% compared to silica which is lower than 12%. Hence, corn stalk is the best adsorbent because of its effectiveness of percentage of heavy metal reduction in aqueous solution compare to silica.